Margin Pemasaran Komoditi Kentang Di Kecamatan Modoinding Kabupaten Minahasa Selatan - Maukar, Orsel; Benu, Noortje Marselianie; Mandei, Juliana Ruth (AGRI-SOSIOEKONOMI, 2024)
The objectives of this study were to map market actors, calculate marketing margins for potato crops, and describe the potato marketing channels in Modoinding Sub-district. The research took place in May 2023 and was conducted in Modoinding District, South Minahasa Regency. Data were collected through primary data by conducting interviews with owners or farmers who cultivate potato crops using a list of questions (questionnaires) that have been prepared. Secondary data were obtained through literature searches from literature, articles, journals, previous research and relevant data and reports from relevant agencies such as the Department of Agriculture, BPS and district, sub-district and village governments to support primary data. Samples were taken from 30 people in 10 villages using simple random sampling and for traders using snowball sampling. The data obtained were analyzed descriptively, and using tables, and described in the form of surveys obtained through direct interaction with research subjects or test subjects using questionnaire techniques. The marketing channels obtained can be described as a whole pattern and level of marketing channels. The results of this study show that the potato marketing margin of each institution in Modoinding sub-district is different between Manado, Bitung, and Kotamobagu channels. Farmer's share received by farmers in the Bitung channel is higher than farmer's share in the Manado and Kotamobagu channels, but farmers still get the same purchase price. Channel (farmer - intermediary - retailer - consumer). Farmers still get the same price and the costs of labor and transportation are borne by buyers, namely collectors and retailers.